2018
DOI: 10.3390/ijerph15081626
|View full text |Cite
|
Sign up to set email alerts
|

Aberrant Driving Behaviour, Risk Involvement, and Their Related Factors Among Taxi Drivers

Abstract: The current study aims to investigate the aberrant driving behaviour and risk involvement of Iranian taxi drivers. The sample comprised 405 Iranian taxi drivers, who were recruited with a cross-sectional design, using a self-completion questionnaire survey during October and November 2016. We contribute to the literature by understanding how and to what extent the socioeconomic, demographic, driving, and aberrant driving behaviours influence risk involvement (accident involvement and traffic tickets). The vali… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
33
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(45 citation statements)
references
References 45 publications
10
33
2
Order By: Relevance
“…As hypothesized (Hypothesis 1) findings supported the relationship between organizational learning and the occurrence of traffic accidents. These findings are consistent with sociotechnical approaches that emphasize the relevance of the organizational factors and its influence on safety [ 4 , 6 , 7 , 8 , 9 ]. Moreover, it is also congruent with previous research conducted in other complex systems (e.g., healthcare or construction) that suggest that organizational learning benefits safety [ 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 ].…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…As hypothesized (Hypothesis 1) findings supported the relationship between organizational learning and the occurrence of traffic accidents. These findings are consistent with sociotechnical approaches that emphasize the relevance of the organizational factors and its influence on safety [ 4 , 6 , 7 , 8 , 9 ]. Moreover, it is also congruent with previous research conducted in other complex systems (e.g., healthcare or construction) that suggest that organizational learning benefits safety [ 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 ].…”
Section: Discussionsupporting
confidence: 89%
“…This study has a number of theoretical implications. Findings supported theoretical postulates on the need to take into account organizational factors such as organizational learning to better understand road safety [ 6 , 7 , 8 ]. In this sense, it encourages future studies to move toward more complex models of traffic accident occurrence in road transport organizations.…”
Section: Discussionsupporting
confidence: 61%
See 1 more Smart Citation
“…81% of taxi drivers in Ankara, Turkey reported talking by using hand-held phone while driving [26]. On the other hand, many previous studies reported in the literature show that professional driver's crash involvement is significantly related to the sociodemographic factors, working conditions or risky driving behaviors [10,15,[27][28][29]; therefore, the proposed quantitative approach using all these possible contributory factors can be used to examine the potential crash risk for professional drivers (i.e., taxi, bus, coach, truck) in China, European countries and other areas in the world [15,30]. The findings of this study provide valuable data with important implications for worldwide decision-making in public health policy and traffic regulation for professional drivers.…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…A score higher than mean value indicated the highest driver errors and violations in driving behaviors. The validity of the DBQ has been validated in numerous studies conducted in Iran [26][27][28].…”
Section: Driver Behavior Questionnaire Measurementmentioning
confidence: 99%